Stai fermo un girone. Un gioco per scoprire Dante e il suo mondo - Barucci, Guglielmo (Milano University Press, 2021)
"Stai fermo un girone" (skip a turn in hell) is a game based on the "Game of the Goose", a traditional children's board game. It is dedicated to Inferno by Dante Alighieri, and to all humanities research focused on the Middle Ages. To advance along the board, and to win the game, one must not only have a certain familiarity with cantos, characters, and themes of Dante's Inferno, but must also be able to tackle different modes of enquiry for the texts used in university studies. In so doing, one can unlock a door through which to view Dante's work, set against the backdrop of the Middle Ages, with its history, ideas, culture, questions raised, and answers given. This board game will help stimulate and further the understanding of secondary school students encountering Dante's verses for the first time. It's also a fun way for aficionados to relive and revisit a beloved writing. Thanks to its three levels of difficulty, the game is suitable for persons of all skill levels, from novices to veterans. The print-cut-play format makes it easy for everyone to build their own set of cards, markers and board, and to immerse themselves in the world of Dante and his Inferno.